CONSUMPTION AND BACTERIAL RESISTANCE TO AMINOGLYCOSIDES AT SUDANESE UNIVERSITY HOSPITAL - Bakheit, Einas A; Elhag, Kamal M; Abduelkarem, Abduelmula R; Basheer, Nada A (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The objective of this study was to describe patterns of antimicrobial resistance to gentamicin (Gen) and amikacin (Ak) among Gram-negative aerobic bacteria during 1-year period and to determine the association between antibiotic resistance and the consumption of Gen. Methods: Aminoglycosides consumption at Soba University Hospital wards was measured and susceptibility of Gram-negative bacteria for the same period was evaluated. Consumption data were converted to defined daily doses (DDDs)/100 bed days based on DDD/anatomical therapeutic chemical the WHO system. The association between the frequency of strains resistant to Gen and Ak and their consumption was assessed by linear regression analysis using Spearman’s correlation. The level of statistical significance was set at p<0.05. Results: A total of 973 Gram-negative isolates were identified and tested for antimicrobial susceptibility to Gen and Ak. Resistance to Gen alone was found to be 19.42%; n=189, resistance to Ak alone was found to be 3.08%; n=30, and resistance to Gen plus Ak was found to be 5.24%; n=51. Pseudomonas aeruginosa was the most resistant pathogen to Ak plus Gen (2.26%; n=22). A positive correlation between the increases in the use of Gen and the prevalence of bacterial resistance among hospital wards was found (correlation coefficient r=0.6; p=0.04). Conclusion: Gen and Ak are still highly active antimicrobial agents for the treatment of aerobic Gram-negative bacteria at times of intensified resistance to other antimicrobial agents. Monitoring the use of aminoglycosides is very important too. Â